Kepemimpinan, budaya organisasi dan kinerja: peran mediasi motivasi kerja - Muchammad Ismail Hamzah; Endi Sarwoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This research aims to analyze the direct relationship between leadership, organizational culture on performance, and to analyze the indirect relationship that is mediated by work motivation. The study used a quantitative approach, namely explanatory research, using a sample of 110 research that were taken randomly from certified teachers at junior high schools in Malang Regency. The data were collected using a questionnaire with a 5 point Likert scale, while the data analysis technique used Path Analysis. The research findings showed that performance was influenced by leadership and work motivation, but the leadership was not proven to affect work motivation. Another research finding is that organizational culture does not significantly contribute to performance, but contributes to work motivation, work motivation only mediates the relationship between organizational culture and performance. The research implication is that to improve performance, effective leadership and work motivation are needed, further increasing work motivation can be achieved from strengthening organizational culture. The next researcher is suggested to test the role of leadership on organizational culture.